Methods of measurement of CSR disclosure level in corporate reporting - Dyduch, Justyna (Research Papers of Wrocław University of Economics, 2018)
In the research on CSR disclosure level in annual, integrated, environmental andCSR reports different methods of measurement of this level based on the content analysis areused. The aim of the paper is to present methods of measurement of CSR disclosure extentand quality applied in practice on the basis of the literature review. The wide diversity ofthese methods on the one hand enables to capture different aspects of CSR reporting leveland on the other hand leads often to difficulties in comparability of various research resultsconcerning disclosure extent and quality and their determinants
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 520; s. 46-45
Keywords: CSR reporting; disclosure; content analysis; sprawozdawczość CSR; ujawnienia; analiza zawartości